Content Analysis of an ESP Textbook; English for Vocational High School - Asti Ramadhani E Lestari; Elyza Martiarini (Pendidikan Bahasa Inggris Universitas Nurul Huda, 2021)
This research aimed at describing the result of English textbook analysis. The textbook is used as a medium for teaching English for Third-Grade students of Vocational Highschool in the second. This analysis verifies the appropriateness of the material that is contained in the book and used as a medium of teaching. The development of